2009
DOI: 10.1039/b816018j
|View full text |Cite
|
Sign up to set email alerts
|

Flow-through functionalized PDMS microfluidic channels with dextran derivative for ELISAs

Abstract: In this work, a dextran modified PDMS microfluidic ELISA device was fabricated. The dextran functionalization was conducted with a simple, economic and fast flow-through process in a fabricated PDMS microfluidic device, and demonstrated significant enhancement of hydrophilicity and efficient covalent immobilization of proteins on the PDMS microchannel surface. The device was used to simultaneously detect multiple important biomarker IL-5, HBsAg, and IgG, showing a limit of detection of 100 pg mL(-1) and a dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
108
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 32 publications
0
108
0
Order By: Relevance
“…However, antibody microarray does not have an effi cient signal amplifi cation method such as PCR used in DNA arrays; its sensitivity currently still cannot meet the requirements for many practical applications such as clinical diagnosis. Inspiring by the enzyme-linked immunosorbent assay, [ 6,7 ] in which the detection signal is specifi cally amplifi ed by an enzymatic reaction, some enzyme-based immunoassay signal amplifi cation methods such as rolling-circle amplifi cation, [ 8 ] tyramide signal amplifi cation, [ 9 ] and enzyme-triggered chemiluminescence [ 10,11 ] have been developed to improve the sensitivity of immunoassays, but often suffer from tedious operations and expensive reagents. Dispersible bioconjugates containing thousands of fl uorescent molecules/luminescent materials with recognition antibodies can deliver strong emissive signals, but their applications are restrained by complicated synthetic procedure and questionable reproducibility.…”
Section: Doi: 101002/adma201403712mentioning
confidence: 99%
“…However, antibody microarray does not have an effi cient signal amplifi cation method such as PCR used in DNA arrays; its sensitivity currently still cannot meet the requirements for many practical applications such as clinical diagnosis. Inspiring by the enzyme-linked immunosorbent assay, [ 6,7 ] in which the detection signal is specifi cally amplifi ed by an enzymatic reaction, some enzyme-based immunoassay signal amplifi cation methods such as rolling-circle amplifi cation, [ 8 ] tyramide signal amplifi cation, [ 9 ] and enzyme-triggered chemiluminescence [ 10,11 ] have been developed to improve the sensitivity of immunoassays, but often suffer from tedious operations and expensive reagents. Dispersible bioconjugates containing thousands of fl uorescent molecules/luminescent materials with recognition antibodies can deliver strong emissive signals, but their applications are restrained by complicated synthetic procedure and questionable reproducibility.…”
Section: Doi: 101002/adma201403712mentioning
confidence: 99%
“…However, this approach requires relatively complex fabrication steps (nanostructure assembly within microchannels). On the other hand, when more simple devices with user-friendly protocols are utilized, such as the chemically-modified polydimethyl(siloxane) (PDMS) microfluidic straight channel ELISA device described by Yu et al or the point-of-care fluorescent immunoassay microchip that requires no external equipment by Hosokawa et al detection limits are equivalent to or higher than that of conventional well plate immunoassays (Yu et al 2009;Hosokawa et al 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Supramolecules such as dextran (Jonsson et al 2008;Yu et al 2009b) and polyethyleneimine (PEI) (Bai et al 2006;Bai et al 2007) have been reported as coating materials that provide multiple active sites for improving protein immobilization efficiency in microchannels. In this scheme, only a monolayer of polymer is randomly anchored on the substrate to introduce limited functional groups.…”
Section: Introductionmentioning
confidence: 99%